If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 3w + -9 Reorder the terms: 42 = -9 + 3w Solving 42 = -9 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 42 + -3w = -9 + 3w + -3w Combine like terms: 3w + -3w = 0 42 + -3w = -9 + 0 42 + -3w = -9 Add '-42' to each side of the equation. 42 + -42 + -3w = -9 + -42 Combine like terms: 42 + -42 = 0 0 + -3w = -9 + -42 -3w = -9 + -42 Combine like terms: -9 + -42 = -51 -3w = -51 Divide each side by '-3'. w = 17 Simplifying w = 17
| 3x+2(3)=4 | | 5-3x=-4[3(x+2)-1] | | 7d=4+6d | | 2(-14/3)-40 | | 9y+4=8y-5 | | -2v/9=-12 | | 8=y/25.6 | | .4(e+5)-.3e=17 | | (5x-1)/1=1 | | 8(4-x)=4(x+5) | | 3x-6.2=14.2 | | -8d=-9d+7 | | 30=-5/2u | | 90=(x+2)(y+1.5) | | 7f/3=5 | | m^2-10m+19=-8 | | 5X+3-X=15+X | | 4c=(a-b)/3 | | 49v^2+16=-56v | | b/3=15.2 | | 10n=7n+9 | | log(132-4x)=2 | | 54=d | | 2x+54=24 | | Cos(5x)=0.8 | | 1200m=600 | | -10+c=-4c | | -(8y-3)-(-7y-8)=9 | | 6n=43 | | 1-2n=-10+5-n+4n | | -5+2a-8a=42 | | 3y+21=6y |